The Diversity of Irony - Athanasiadou, Angeliki; Colston, Herbert L. (Cognitive linguistics research ;, 2020)
Although the figure of irony has enjoyed extensive attention through important contributions to the diverse literatures addressing figurative thought and language, it still remains relatively in the background compared to other figures such as metaphor and metonymy. The present volume, together with a 2017 collection by Angeliki Athanasiadou and Herbert L. Colston, aims to the further exploration of verbal and situational irony, its gestural accompaniments, its comprehension and interpretation, its constructional diversity and its cooperation with other figures such as metaphor and hyperbole. The present volume is a highly interesting collection of chapters dealing with both theoretical investigations and descriptive applications of a central figure pervading human thought and language. Its aim is to draw more attention to irony's diversity and its concomitant connections to other aspects of figurativeness.